Uji Potensi Hasil Beberapa Galur Padi Gogo - Eko Sulistyono; M. A. Chozin; Femila Rezkiyanti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2002)
Artificial shading experiment was conducted to test upland rice lines yield potential and study agronomic character correlated with high yield. A factorial experiment was arranged in split plot design with three replications. The main plot were three levels of shading: 0%, 25% and 50%. The sub-plot were 18 upland rice lines. Dry grain weight was affected by interaction between shading and lines. High yield was resulted by B8503E-TB-19B-3-4, .S'3605F-PN-201, IGM440, and 2GM440. Agronomic characters correlated with high yield potential at low light intensity were high plant, high leaf area, low tiller number, high shoot and root dry weight, high grain density and low unfilled grain percentage. Key words: Agronomic character, Grain density, Root weight, Low light intensity.